DEBTOR PROTECTION IN THE EXECUTION OF FIDUCIA SECURITIES - Ratih Mega Puspasari; Muhammad Ngazis (UNISSULA, 2021)
In its development, economic needs and economic pressure cannot release every human being from his dependence on loan guarantee institutions. Fiduciary collateral institutions are not excluded, however, in its development, the installment payment process often fails, requiring that fiduciary collateral be executed to be taken by creditors, while the method of execution often uses debt collection services with a violent approach. The approach method used in this paper is an empirical juridical method where legal issues are analyzed from the normative and empirical aspects.